The ADAMs family of proteins: from basic studies to potential clinical applications - Duffy, Michael J.; Lynn, David J.; Lloyd, Andrew T.; O’Shea, Caroline M. (Thrombosis and Haemostasis, 2003)
The ADAMs are a family of membrane proteins possessing a disintegrin and metalloprotease domain. Currently,34 members are known to exist. Approximately 50% of the ADAMs contain a metalloprotease-like domain and some of these have been shown to possess protease activity. Most of the protein substrates identified to date for ADAMs are either integral membrane or extracellular matrix (ECM) proteins. In addition to hydrolysing proteins, a number of ADAMs bind to integrins. The attachment to integrins occurs via the disintegrin domain. Since the ADAMs can play a role in both proteolysis and adhesion, they have been implicated in a variety of biological processes such as sperm-egg fusion, somatic cell-cell adhesion, ecto-domain shedding, myoblast fusion and development. Altered expression of certain ADAMs has been associated with a number of diseases including asthma, arthritis, Alzheimer’s disease, atherosclerosis and cancer.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: ADAMs; cell adhesion; disease and metalloproteinases